THE CONCEPT OF HAROKAH IN ISLAMIC EDUCATION ACCORDING TO SAYYID QUTB - Shobrun Jamil; Usiono Usiono (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this paper is to introduce the concept of harokah in Islamic education which was initiated by Sayyid Qutb. By using library research method, this research produces several harokah ideas related to Islamic education. One of them is according to Sayyid Qutb, Education is the movement of one's life, every movement of one's steps is worship that must be decorated with the value of monotheism. The purpose of education also in the conception of harokah is how he becomes a servant of Abdullah and the caliph who should have the ability to become a politically literate person, which in the end also leads to an Islamic education curriculum that combines religious, social, political history and social education. Education is like harakat in ahruf hijaiyyah, sometimes it becomes fathah with firmness for a teacher, when he becomes a student let him be like harokat kasroh, be a person who is humble, and harakat dommah also directs to education it is like knowledge that must be practiced and taught in accordance with Hadith of the Prophet Muhammad SAW. Sukun also refers to the meaning that sometimes to gain knowledge, we have to reflect and ask God, sukun does not mean death but is tabadulul a'mal or job change.Keywords: Sayyid Qutb, Islamic education, harakat, tabadulul a'mal.